Is There Another Posterior Approach for Presacral Tumors Besides the Kraske Procedure? — A Study on the Feasibility and Safety of Surgical Resection of Primary Presacral Tumors via Transsacrococcygeal Transverse Incision - Zhao, Xudong; Zhou, Sixin; Liu, Na; Li, Peiyu; Chen, Lin (Frontiers in Oncology, 2022)
Background: The aim of the present study was to explore the feasibility and safety of the surgical resection of presacral tumors via a transsacrococcygeal transverse incision. Methods: The clinical data and prognoses of patients with presacral tumors who underwent surgery at the Chinese People’s Liberation Army (PLA) General Hospital between January 2009 and December 2018 were retrospectively reviewed and analyzed. Results: A total of 110 patients with presacral tumors were included in this study, including 82 female patients and 28 male patients, with a female-to-male ratio of 2.9:1. A posterior approach (transsacrococcygeal transverse incision) was utilized in 105 patients, an anterior approach (transabdominal excision) was utilized in 1 patient, and a combined (posterior plus anterior) approach was utilized in 4 patients. The mean tumor size was 8.72±4.28 cm. More than half of the patients (n=59/110) with presacral tumors were asymptomatic. Twenty-six pathological types were observed in our study, including 96 benign lesions and 14 malignant lesions. The intraoperative complication rate was 42.7% (n=47/110), whereas the postoperative morbidity rate was 3.6% (n=4/110). The length of hospital stay for patients treated with the posterior approach was shorter than that of patients treated with the anterior and combined approaches. After a mean follow-up of 90.13±31.22 months, 11 patients had local presacral tumor recurrence, and 1 patient had distant metastasis, with a combined recurrence rate of 10.9% (n=12/110). Conclusions: The surgical resection of primary presacral tumors via a transsacrococcygeal transverse incision is feasible and safe, with acceptable oncological therapeutic outcomes and a low postoperative morbidity rate, making it worth popularizing in clinical practice.